Urinary Sodium and Potassium Excretion, Mortality, and Cardiovascular Events - O'Donnell, Martin; Mente, Andrew; Rangarajan, Sumathy; McQueen, Matthew J; Wang, Xingyu; Liu, Lisheng; Yan, Hou; Lee, Shun Fu; Mony, Prem; Devanath, Anitha; Rosengren, Annika; Lopez-Jaramillo, Patricio; et al. (The New England journal of medicine, 2014)
In a large study in 17 countries, an estimated sodium intake that was either higher or lower than the average estimated sodium intake was associated with an increased risk of cardiovascular events. A higher-than-average potassium intake was associated with reduced risk. Most of the global population consumes between 3.0 and 6.0 g of sodium per day (7.5 to 15.0 g of salt per day). 1 , 2 Guidelines on cardiovascular disease prevention recommend a maximum sodium intake of 1.5 to 2.4 g per day, but achieving this target will require a substantial change in diet for most people. 3 – 5 Although clinical trials have shown a reduction in blood pressure with a reduced sodium intake, to our knowledge, no large randomized trial has been conducted to document reductions in the risk of cardiovascular disease with low sodium intake. 6 Prospective cohort studies have shown inconsistent . . .